Academic Leadership of School Administrators Affecting Learning Organizations in Schools under Chanthaburi Primary Educational Service Area Office 2 - ธนูรักษ์, สมเกียรติ; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The findings revealed that the overall level of academic leadership of school administrators was at a high level, and the overall level of learning organization in schools was also at a high level. Academic leadership of school administrators had a positive relationship with learning organization in schools at the .01 level of statistical significance. Moreover, academic leadership of school administrators significantly predicted learning organization in schools. The results of this study be used as guidelines for developing academic leadership of school administrators and promoting schools as effective and sustainable learning organizations. The findings of this study revealed that the overall level of academic leadership of school administrators was at a high level. However, the aspect of formulating vision, goals, and mission demonstrated the lowest mean score. Therefore, school administrators should encourage teachers to actively participate in establishing clear and shared vision, goals, and mission of the school. Additionally, administrators should set high performance expectations for both teachers and students and enhance communication to ensure a common understanding of these directions.            Furthermore, the overall level of educational institutions as learning organizations was also found to be at a high level. Nevertheless, systems thinking had the lowest mean score among all aspects. This indicates that administrators should promote effective prioritization before task implementation, support comprehensive and appropriate planning for school quality development, and encourage teachers to observe, analyze, and utilize data to construct knowledge independently.            In addition, the study found that academic leadership of school administrators had a strong positive correlation with the development of learning organizations in educational institutions (r= 0.960). Moreover, academic leadership significantly predicted the development of learning organizations at a statistically significant level.            The findings of this study can be applied as practical guidelines for enhancing academic leadership and fostering a supportive academic environment within schools. Since the promotion of an academic atmosphere showed the lowest mean score, administrators should emphasize setting academic goals that focus on student achievement, providing supportive learning environments through rewards and recognition for high-achieving students, promoting academic activities, and advancing educational institutions toward becoming effective and sustainable learning organizations.